Verification and Data Processing of Open Data for Data-Driven News Stories in Lokadata.id and Katadata.co.id - Amalia Nurul Muthmainnah; Maulana Arief; Nurul Fitriyani (Jurnal Kajian Jurnalisme, 2022)
With the existence of open data, journalists have additional investigative tools to report on issues in the public interest and to hold the government to account. However, it remains outside the mainstream of journalism due to the limitation to access and work with data. The open data initiative in Indonesia has started since 2010. Adhering to UU No. 14 Tahun 2008 about Public Information Openness, Indonesia has implemented an open data portal, called Satu Data Indonesia in 2019. There are indeed a handful of studies that examine the implementation of open data portals in Indonesia. However, only a few studies have given attention to how data journalists are using these data and their perceptions about the quality of data provided by the government. This study uses a descriptive qualitative approach and collects data through semi-structured in-depth interviews. It is intended to see the process on how data journalists in Indonesia turn data to news stories. By studying Lokadata.id and Katadata.co.id, we found that data provided by the authority sources (government) are still the main sources for data journalists in Indonesia. Despite the fact that the quality of data is getting better, most journalists in this study argued that the government’s open data has not yet integrated and has no basic standard that is collectively used. Therefore, the verification process and data processing in each media is important. The most common ways that journalists use to verify the data are by exploring the raw data, contacting the institution that provided the data, and considering the reputation of the data sources. However, there is a tendency of data journalists to be passively relying on official sources and ‘hide behind’ the perceived credibility of their sources.